A Genome-Wide Association Study Identifies UTRN Gene Polymorphism for Restless Legs Syndrome in a Korean Population - Cho, Chul-Hyun; Choi, Ji-Hye; Kang, Seung-Gul; Yoon, Ho-Kyoung; Park, Young-Min; Moon, Joung-Ho; Jung, Ki-Young; Han, Jin-Kyu; Shin, Hong-Bum; Noh, Hyun Ji; Koo, Yong Seo; Kim, Leen; et al. (Psychiatry investigation, 2017)
Restless legs syndrome (RLS) is a highly heritable and common neurological sensorimotor disease disturbing sleep. The objective of study was to investigate significant gene for RLS by performing GWA and replication study in a Korean population. We performed a GWA study for RLS symptom group (n=325) and non-RLS group (n=2,603) from the Korea Genome Epidemiology Study. We subsequently performed a replication study in RLS and normal controls (227 RLS and 229 controls) to confirm the present GWA study findings as well as previous GWA study results. In the initial GWA study of RLS, we observed an association of rs11645604 (OR=1.531, p=1.18×10 ) in on chromosome 16q23.3, rs1918752 (OR=0.6582, p=1.93×10 ) and rs9390170 (OR=0.6778, p=7.67×10 ) in on chromosome 6q24. From the replication samples, we found rs9390170 in (p=0.036) and rs3923809 and rs9296249 in (p=0.045, p=0.046, respectively) were significantly associated with RLS. Moreover, we found the haplotype polymorphisms of rs9357271, rs3923809, and rs9296249 (overall p=5.69×10 ) in was associated with RLS. From our sequential GWA and replication study, we could hypothesize rs9390170 polymorphism in is a novel genetic marker for susceptibility to RLS. Regarding with utrophin, which is encoded by , is preferentially expressed in the neuromuscular synapse and myotendinous junctions, we speculate that utrophin is involved in RLS, particularly related to the neuromuscular aspects.